2000
DOI: 10.1046/j.1365-2044.2000.055002137.x
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the staffing level required for a high‐dependency unit

Abstract: SummaryHigh-dependency units are increasing in number and becoming an ever more important part of a hospital's facilities. The optimum staf®ng ratio is unknown, but the Department of Health and the Intensive Care Society recommend a level of one nurse to two patients. We recorded Therapeutic Intervention Scoring System-28 scores and Nurse Dependency Scores for all admissions to our adult, general high-dependency unit over 7 months. We found a weak correlation between the nurse dependency score and the Therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 14 publications
0
20
0
1
Order By: Relevance
“…26,[28][29][30][31][32] The mean age of patients hospitalized in type 2 and 3 ICUs in Poland was similar to the lower value of 52, whereas the mean age of patients in type 1 ICUs (61.32 years) was similar to the higher value.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…26,[28][29][30][31][32] The mean age of patients hospitalized in type 2 and 3 ICUs in Poland was similar to the lower value of 52, whereas the mean age of patients in type 1 ICUs (61.32 years) was similar to the higher value.…”
Section: Discussionmentioning
confidence: 54%
“…In Western Europe and the United States, mean ICU length of stay is 1 to 78 days. 26,28,[30][31][32][33] The greatest mean ICU length of stay in the hospitals in our study, nearly 34 days, occurred in type 3 ICUs, ones where advanced and complicated procedures are performed. Mean ICU length of stay was 20 days in type 2 (voivodeship) hospitals and no more than 8 days in type 1 (poviat) hospitals, where basic procedures are performed.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…It was also shown that using a TISS-28 of on average 23 and a nursing dependency score of on average 1.0, cover of at least 1:2 would have been required [27].…”
Section: Key Statementmentioning
confidence: 99%
“…The factors that impact on ICU bed availability are varied. Staffi ng 9,17,19 , admission and discharge decisions 2,9,20,17,14,21 , open versus closed ICUs 22,23 , seasonal peaks in ICU bed demand and the presence of high dependency units (HDUs) 24,25,26 potentially infl uence occupancy rates. While premature discharge has received some attention 2,9,10,11 , one factor that is rarely considered in the study of occupancy rates is the impact of discharge delay time on subsequent ICU bed availability.…”
mentioning
confidence: 99%